State, space, world : selected essays - Lefebvre, Henri, 1901-1991 (University of Minnesota Press, 2009)
"One of the most influential Marxist theorists of the twentieth century, Henri Lefebvre pioneered the study of the modern state in an age of accelerating global economic integration and fragmentation. Shortly after the 1974 publication of his landmark book The Production of Space, Henri Lefebvre embarked on one of the most ambitious projects of his career: a consideration of the history and geographies of the modern state through a monumental study that linked several disciplines, including political science, sociology, geography, and history. State, Space, World collects a series of Lefebvre's key writings on the state from this period. Making available in English for the first time the as-yet-unexplored political aspect of Lefebvre's work, it contains essays on philosophy, political theory, state formation, spatial planning, and globalization, as well as provocative reflections on the possibilities and limits of grassroots democracy under advanced capitalism. State, Space, World is an essential complement to The Production of Space, The Urban Revolution, and The Critique of Everyday Life. Lefebvre's original and prescient analyses that emerge in this volume are urgently relevant to contemporary debates on globalization and neoliberal capitalism"--Provided by publisher